2023
DOI: 10.1021/acs.jpca.2c07358
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Dissociation of Neopentanol: Shock Tube/Photoionization Mass Spectrometry Studies

Abstract: The pyrolysis mechanism of 2,2-dimethyl­propan-1-ol (neopentanol) has been investigated at high temperatures (1128–1401K) and high pressures (5 and 15 bar). The experiments were performed in a miniature shock tube coupled to a time-of-flight mass spectrometer. Cations were generated by tunable vacuum ultraviolet photoionization resulting in multidimensional data sets containing mass and photoionization spectra and the time histories of species. At the elevated temperatures and pressures of this work, neopentan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…21 The pyrolysis of neopentanol, a further alternative alcohol fuel, was investigated by Banyon and Tranter in a miniature shock tube coupled to a time-of-flight mass spectrometer. 22 Although roaming radical reactions had previously been identified for the structurally similar neopentane, the authors found no experimental evidence for these reactions in the pyrolysis of neopentanol at the studied pressures of 5 and 15 bar. 22 Low-temperature reactions in the oxidation of limonene, a potential biojet fuel, and the formation of highly oxygenated intermediates is the subject of the contribution by Dbouk et al 23 They used a sophisticated combination of Fourier transform infrared spectroscopy and high-resolution Orbitrap mass spectrometry with either electrospray ionization or atmospheric pressure chemical ionization, upon direct injection or after prior separation by ultrahigh-performance liquid chromatography, to identify a large number of C x H y O z species with up to five oxygen atoms.…”
Section: ■ Molecules and Reactionsmentioning
confidence: 84%
See 2 more Smart Citations
“…21 The pyrolysis of neopentanol, a further alternative alcohol fuel, was investigated by Banyon and Tranter in a miniature shock tube coupled to a time-of-flight mass spectrometer. 22 Although roaming radical reactions had previously been identified for the structurally similar neopentane, the authors found no experimental evidence for these reactions in the pyrolysis of neopentanol at the studied pressures of 5 and 15 bar. 22 Low-temperature reactions in the oxidation of limonene, a potential biojet fuel, and the formation of highly oxygenated intermediates is the subject of the contribution by Dbouk et al 23 They used a sophisticated combination of Fourier transform infrared spectroscopy and high-resolution Orbitrap mass spectrometry with either electrospray ionization or atmospheric pressure chemical ionization, upon direct injection or after prior separation by ultrahigh-performance liquid chromatography, to identify a large number of C x H y O z species with up to five oxygen atoms.…”
Section: ■ Molecules and Reactionsmentioning
confidence: 84%
“…Burnett et al studied the pyrolysis chemistry of 2-propanol, a promising alternative fuel in the alcohol family, in a rapid compression machine at elevated pressures and moderate temperatures, using fast-gas sampling and gas chromatography for species detection . The pyrolysis of neopentanol, a further alternative alcohol fuel, was investigated by Banyon and Tranter in a miniature shock tube coupled to a time-of-flight mass spectrometer . Although roaming radical reactions had previously been identified for the structurally similar neopentane, the authors found no experimental evidence for these reactions in the pyrolysis of neopentanol at the studied pressures of 5 and 15 bar …”
Section: Fuels and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation